A New Perspective on the Multidimensionality of Divergent Thinking Tasks - Forthmann, Boris; Bürkner, Paul-Christian; Szardenings, Carsten; Benedek, Mathias; Holling, Heinz (Frontiers in Psychology, 2019)
In the presented work, a shift of perspective with respect to the dimensionality of divergent thinking tasks is introduced moving from the question of multidimensionality across divergent thinking scores (i.e., fluency, flexibility, or originality) to the question of multidimensionality within one holistic score of divergent thinking performance (i.e., snapshot ratings of creative quality). We apply IRTree models to test whether unidimensionality assumptions hold in different task instructions for snapshot scoring of divergent thinking tests across Likert-scale points and varying levels of fluency. It was found that evidence for unidimensionality across scale points was stronger with be-creative instructions as compared to be-fluent instructions which suggests better psychometric quality of ratings when be-creative instructions are used. In addition, creative quality latent variables pertaining to low-fluency and high-fluency ideational pools shared around 50% of variance which suggests both strong overlap and evidence for differentiation. The presented approach allows to further examine the psychometric quality of subjective ratings and to examine new questions with respect to within-item multidimensionality in divergent thinking.